Total and Unbound Doravirine Concentrations and Viral Suppression in CSF. (21st September 2021) - Tiraboschi, Juan; Scévola, Sofia; Penchala, Sujan Dilly; Challenger, Elisabeth; Else, Laura; Prieto, Paula; Saumoy, Maria; Imaz, Arkaitz; Silva-Klug, Ana; Niubó, Jordi; Soriano, Irene; Khoo, Saye; et al.
Abstract: We determined total and unbound concentrations of doravirine (DOR) in cerebrospinal fluid and blood plasma. Total and unbound DOR concentrations in cerebrospinal fluid exceeded the half-maximal effective concentration against wild-type virus (5.1 ng/mL) in all patients, suggesting that DOR may contribute to inhibit viral replication in this compartment.